Overcoming Cyberbullying with Empathy: The ‘Weirdos’ Film Shows How Patience and Strong Character Matters - Indrani Dewi Anggraini; Nani Nuraini Sarah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Bullying seriously violates the ethics of human relations. It is a serious problem that affects the mental health of young people, and sadly at times, it can even result in the tragic death of the victims. The act of bullying in the form of gossiping, mocking, laughing at them, or even